Tourism in Porto's Historic Centre: Analysing risks and safeguarding of the landscape - Freitas, Isabel Vaz de (2019)
Tourism in Porto has been growing accompanied by some changes in the city dynamics. In this context, more risks related to the intensive use of city spaces and services to arise. The increase in the annual number of visitors in the city demands a special attention to protect the landscape and urban elements and preserve the city's identity, originality and diversity. Therefor, this study aimed to analyse the visitor's perception of the urban landscape to identify necessary actions to be taken for the sustainable tourism development in Porto. Seven dimensions of the urban landscape were studied in this research, including the pedestrian directional signalling, outdoor advertising, street furniture, green spaces, city traffic, influx of tourists , and conservation status of buildings, monuments and museums. A total of 150 valid surveys were collected from visitors from thirty-one different countries. The results indicated that respondents were satisfied with the city's environment, monuments and culture. However, low satisfaction indicators on dimensions regarding the traffic, green spaces and the conservation of buildings suggest the need to make new regulations by the city's decision-makers.